2019
DOI: 10.1080/13685538.2019.1678581
|View full text |Cite
|
Sign up to set email alerts
|

Results of purified micronized flavonoid fraction in the treatment of categorized type III chronic pelvic pain syndrome: a randomized controlled trial

Abstract: Verit (2020) Results of purified micronized flavonoid fraction in the treatment of categorized type III chronic pelvic pain syndrome: a randomized controlled trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…showed that a double dose of MPFF (1000 mg twice daily) in the first month of treatment provides a quicker resolution of symptoms [ 89 ]. Interestingly, MPFF also reduces CPP caused by prostatitis occurring as a result of increased venous return through the perineum [ 90 ].…”
Section: Treatmentmentioning
confidence: 99%
“…showed that a double dose of MPFF (1000 mg twice daily) in the first month of treatment provides a quicker resolution of symptoms [ 89 ]. Interestingly, MPFF also reduces CPP caused by prostatitis occurring as a result of increased venous return through the perineum [ 90 ].…”
Section: Treatmentmentioning
confidence: 99%